Moishe Postone’s Theory of the Value-Form versus the Expanded Theory of Production/Reproduction of Life under Capitalism - Aranco, Agustín (2025)
The article approaches two contemporary critical perspectives, partially aligned with the philosophical-social legacy of the Frankfurt School, such as the theory of the value form of Moishe Postone and the theory of dynamic stabilization of Hartmut Rosa. Specifically, he argues that while the first is based on a conceptualization of historically specific social forms that models the structural foundations of the production/reproduction of life in capitalism, the second incorporates materialist concerns that collaborate with the updating of the Marxian critique of political economy based on the main challenges that currently dictates the planetarian condition.